Effects of concomitant proton pump inhibitor use on immune checkpoint inhibitor efficacy among patients with advanced cancer. (1st January 2021) - Qin, Bao-Dong; Jiao, Xiao-Dong; Zhou, Xin-Cheng; Shi, Bin; Wang, Jian; Liu, Ke; Wu, Ying; Ling, Yan; Zang, Yuan-Sheng
ABSTRACT: Background: The present study aimed to evaluate the effects of concomitant proton pump inhibitor (PPI) use on immune checkpoint inhibitor (ICI) efficacy among advanced cancer patients. Methods and Materials: A systematic literature search of electronic database was performed to identify all potential reports. Then, meta-analyses were conducted to obtain pooled HRs with 95% CIs, which reveal the influence of PPI use on PFS and OS in patients receiving ICI treatment. Results: A total of 7 studies with 3, 647 advanced cancer patients fulfilled the inclusion criteria. The impact of PPI use was then evaluated on 3, 340 patients for PFS and 3, 647 patients for OS. Concomitant PPI use has a detrimental effect on the efficacy of ICIs that PPI use increased the risk of progression by 28% (HR = 1.28, 95% CI 1.17–1.40; I2 = 31.3%, Q test P = .21) when compared to those not receiving PPIs. Similarly, the meta-analysis showed that PPI use was also associated with shorter OS of advanced cancer patients receiving ICIs that PPI use increased risk of death by 39% (HR = 1.39, 95% CI 1.26–1.54; I2 = 36.5%, Q test P = .16). Sensitivity analysis showed that the pooled HRs were constant after excluding one study at a time, and no significant publication biases were detected. Conclusion: The meta-analysis suggested that concomitant PPI use is significantly associated with low clinical benefit in ICI treatment, revealing a significantly reduced PFS and OS in advanced cancer patients receiving ICIs who are also exposed to PPI.